PENGARUH FAKTOR LOKASI, KELENGKAPAN PRODUK DAN HARGA TERHADAP PEMBELIAN ULANG KONSUMEN (Studi Kasus pada Hypermart Malang Town Square) - Nurhasan Aripin; Rois Arifin; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTPhenomenon that occurs when this location, completeness of the products and the prices ofmost major discussion in this study because it is able to contribute to the purchase of aconsumergood birthday are individually as well as collectively in doing marketing strategy.Research conducted at Hypermart Malang Town Square. Purposes of this research isto test and know the influence factors of location, price and product completeness againstrepeated purchases consumers partially or simultaneous.Variables used in the study wasthe location, the completeness of the product and the price as the independent variable andthe variable purchase re consumers as the dependentvariable. The samples used in thestudy was the unfortunate Hypermart consumer Town Squareas much as 99 respondentsusing a purposive sampling method. Data collection methods the research by disseminatinga questionnaire. The analysis used include: test instruments, test the assumptions ofclassical linear regression testmultiple hypothesis and test by using SPSS 14.0 program forwindows.The results showed a significant effect against the location of purchase consumerreset, completeness of influential products significantly to re-purchase consumers andprices do not affect significantly to restart consumer purchase, location, productcompleteness and simultaneous price effect on the purchase of ullang consumers.Keywords`: Location, Price, Product Completeness, Repeated Purchases ConsumersOcation, Price And Product Completeness Against RepeatedpurchasesConsumers